Predator size influences intraspecific multiple predator effects in swimming crab-Manila clam system - Sun, Yunfei; Wang, Fang; Yang, Chao; Liu, Dapeng; Wang, Xin; Su, Xianpeng (Aquaculture, 2018)
Interactions between multiple predators, whether conspecific or interspecific, has been the subject of many researches. There is a shortage of studies investigating how different size classes of a single species interact with one another to generate multiple predator effects. Here, we used a comprehensive experimental design, consisting of calculation of per capita consumption rates, to examine multiple predator effects on prey when swimming crabs (Portunus trituberculatus) of multiple sizes foraged on manila clams (Ruditapes philippinarum) using a video recording analysis system in the laboratory. We identified multiple predator effects on prey by comparing observed predation rate to that predicted from the multiple risk model. The observed predation rate of crab was significantly lower than predicted value when a conspecific competitor appeared. Swimming crab significantly decreased foraging time budgets when a conspecific competitor appeared. The proportion of time medium-sized crabs spent searching for and handling clam decreased in the presence of competitors. The encounter rate between crabs and clam decreased while the probability of capture upon encounter and the probability of consumption upon capture increased when a conspecific competitor appeared. The handling time per clam significantly decreased when a conspecific competitor appeared. Most encounters between crabs were fighting (2.31–4.14 times/h), secondly chasing (1.02–3.07 times/h), and threatening (1.24–2.09 times/h), and the fewest encounters were non-aggression (0.13–0.49 times/h). The results indicated that swimming crab foraging behavior was affected by the chasing, threatening and fighting behavior of a conspecific competitor and this affected the predation rate on prey, which led to non-independent multiple predator effects in the swimming crab-Manila clam system. •Crab significantly decreased foraging time budgets when competitors appeared.•The handling time per clam significantly decreased when competitors appeared.•The most encounters between crabs were fighting and the fewest encounters were non-aggression behavior.•There is non-independent multiple predator effects in this predation system.